Enabling high rate performance of Ni-rich layered oxide cathode by uniform titanium doping. (September 2019) - Sun, Huabin; Cao, Zhilin; Wang, Tengrui; Lin, Rui; Li, Yuyu; Liu, Xi; Zhang, Lulu; Lin, Feng; Huang, Yunhui; Luo, Wei
Abstract: Ni-rich layered oxides (LiNi1- x-y Co x Mn y O2, 1- x - y  ≥ 0.5) are attracting great attention due to their high capacity and operating voltage. However, Ni-rich layered oxides still face long-standing challenges, such as incomplete capacity release and fast capacity fade, especially at high C rates. Herein, we implement a wet chemical method to dope Ti into LiNi0.8 Co0.1 Mn0.1 O2 (NCM811). We discover that NCM811 with the homogeneously distributed Ti can effectively enhance ion transfer kinetics and thus greatly improve capacity delivery at high C rates. The Ti-doped NCM811 exhibits a capacity of 196 mAh/g and 157 mAh/g at 0.5C and 2C in voltage range of 2.8–4.6 V, 5% higher (188 mAh/g at 0.5C) and 15% higher (136 mAh/g at 2C) than the pristine NCM811. Ti-doped NCM811 cathodes also exhibit enhanced cycling stability with capacity retention of 84% after 100 cycles at 1C, which shows that our methodology for Ti doping is potentially competitive for a practical production of Ni-rich layered oxides. Highlights: A simple, low cost and scalable hydrolysis method has been developed to uniformly dope Ti into Ni-rich layered oxide. Ni 2+ /Li + cation mixing degree has been decreased. Fast Li ion transport kinetics and stable structure has been enabled. A much better rate capability and significantly enhanced cycle stability have been offered.